Integrated bioinformatics analysis reveals that OPRK1 inhibits ferroptosis and induces enzalutamide resistance in prostate cancer - Liangrong Zhang; Yanqin Liu; Xiaodong Wen; Xiangkai Zhang; Peng Fan; Xiaoming Cao (European Journal of Medical Research)
Abstract Enzalutamide (Enz) is employed in the management of castration-resistant prostate cancer (CRPC). However, a substantial subset of patients may develop resistance to Enz, thereby reducing its therapeutic effectiveness. The underlying mechanisms contributing to the development of Enz resistance in PCa, whether arising from androgen deprivation or the burden of Enz treatment, remain inadequately understood. OPRK1 plays a key role in Enz resistance through ferroptosis inhibition, which is detected by the analysis of Gene Expression Omnibus (GEO) databases. Silencing OPRK1 via small interfering RNA (siRNA) resulted in the activation of ferroptosis signaling in LNCaP cells. These findings indicate that OPRK1 significantly contributes to Enz resistance in PCa and may serve as a promising therapeutic target for resistant patients. Graphical Abstract